Antibody–drug conjugate bioanalysis using LB-LC–MS/MS hybrid assays: strategies, methodology and correlation to ligand-binding assays. (July 2016) - Wang, Jian; Gu, Huidong; Liu, Ang; Kozhich, Alexander; Rangan, Vangipuram; Myler, Heather; Luo, Linlin; Wong, Richard; Sun, Huadong; Wang, Bonnie; Vezina, Heather E; Deshpande, Shrikant; et al.
Background: Antibody–drug conjugates (ADCs) are complex drug constructs with multiple species in the heterogeneous mixture that contribute to their efficacy and toxicity. The bioanalysis of ADCs involves multiple assays and analytical platforms.Methods: A series of ligand binding and LC–MS/MS (LB-LC–MS/MS) hybrid assays, through different combinations of anti-idiotype (anti-Id), anti-payload, or generic capture reagents, and cathepsin-B or trypsin enzyme digestion, were developed and evaluated for the analysis of conjugated-payload as well as for species traditionally measured by ligand-binding assays, total-antibody and conjugated-antibody.Results & conclusion: Hybrid assays are complementary or viable alternatives to ligand-binding assay for ADC bioanalysis and PK/PD modeling. The fit-for-purpose choice of analytes, assays and platforms and an integrated strategy from Discovery to Development for ADC PK and bioanalysis are recommended.